Preclinical Evaluation of 99mTc-Labeled GRPR Antagonists maSSS/SES-PEG2-RM26 for Imaging of Prostate Cancer - Ayman Abouzayed; Sara S. Rinne; Hamideh Sabahnoo; Jens Sörensen; Vladimir Chernov; Vladimir Tolmachev; Anna Orlova (MDPI AG, 2021)
Background: Gastrin-releasing peptide receptor (GRPR) is an important target for imaging of prostate cancer. The wide availability of single-photon emission computed tomography/computed tomography (SPECT/CT) and the generator-produced 99mTc can be utilized to facilitate the use of GRPR-targeting radiotracers for diagnostics of prostate cancers. Methods: Synthetically produced mercaptoacetyl-Ser-Ser-Ser (maSSS)-PEG2-RM26 and mercaptoacetyl-Ser-Glu-Ser (maSES)-PEG2-RM26 (RM26 = d-Phe-Gln-Trp-Ala-Val-Gly-His-Sta-Leu-NH2) were radiolabeled with 99mTc and characterized in vitro using PC-3 cells and in vivo, using NMRI or PC-3 tumor bearing mice. SPECT/CT imaging and dosimetry calculations were performed for [99mTc]Tc-maSSS-PEG2-RM26. Results: Peptides were radiolabeled with high yields (>98%), demonstrating GRPR specific binding and slow internalization in PC-3 cells. [99mTc]Tc-maSSS-PEG2-RM26 outperformed [99mTc]Tc-maSES-PEG2-RM26 in terms of GRPR affinity, with a lower dissociation constant (61 pM vs 849 pM) and demonstrating higher tumor uptake. [99mTc]Tc-maSSS-PEG2-RM26 had tumor-to-blood, tumor-to-muscle, and tumor-to-bone ratios of 97 ± 56, 188 ± 32, and 177 ± 79, respectively. SPECT/CT images of [99mTc]Tc-maSSS-PEG2-RM26 clearly visualized the GRPR-overexpressing tumors. The dosimetry estimated for [99mTc]Tc-maSSS-PEG2-RM26 showed the highest absorbed dose in the small intestine (1.65 × 10−3 mGy/MBq), and the effective dose is 3.49 × 10−3 mSv/MBq. Conclusion: The GRPR antagonist maSSS-PEG2-RM26 is a promising GRPR-targeting agent that can be radiolabeled through a single-step with the generator-produced 99mTc and used for imaging of GRPR-expressing prostate cancer.